(untitled) (Sustainability in Debate, 2021)
Hydropower generation is responsible for supplying most of the electricity in Brazil. Like other renewable sources, water is highly sensitive to meteorological variables, so that climate change may have a considerable impact on it. Therefore, this study aims at assessing climate change impacts on hydropower generation and their consequences for the Brazilian electricity system. Scenario data for specific average global warming levels of 2°C and 4°C from Eta_HadGEM2-ES and Eta_MIROC5 downscaled climate models are used. Outcomes indicate that the electricity system’s adaptive capacity to lower hydropower generation includes a growing share of other renewable and natural gas fired thermoelectric generation, increasing the system’s marginal cost to meet projected demand in 2030. Greenhouse gas emissions are projected to increase in a 2°C scenario, but to decrease in scenarios in which warming reaches 4°C.